Les Complications Osseuses au Cours de la Drepanocytose au Service d’Hematologie-Oncologie du CHU de Donka de Conakry - Mamady, Diakite; Sayon, Kante Ansoumane; Alhassane, Dambakate; Moussa, Bathily; Djongbe, Camara; Aissata, Tolo-Diebkile (European Scientific Journal, ESJ, 2019)
Introduction: Sickle cell disease has an evolution characterized by acute and chronic complications that affect almost all the target organs of the body (bones, eyes, heart, kidneys, brain ...). The purpose of this study was to describe the bone complications of sickle cell disease. Patients and Methods: This was a retrospective study performed in the HematologyOncology Department of the Donka Teaching Hospital over a five-year period (5 years) from 1 January 2011 to 31 December 2015. Results: The frequency of bone complication of sickle cell disease was 15%. There was a predominance of the female sex with the sex ratio of 0.8. The average age of the patients was 27.5 years with extremes of 10 and 50 years. The main reason for consultation was bone pain found in 100% of our patients. Osteomyelitis was the most frequent 55.56%, followed by Necrosis of the femoral head 44.44%. Conclusion: The study found that the prevalence of bone complications is not negligible. A prospective and analytical study with a larger sample would be required to identify risk factors and develop a management protocol. Introduction : la drépanocytose a une évolution caractérisée par des complications aiguës et chroniques qui intéressent presque tous les organes cibles de l’organisme (os, yeux, cœur, reins, cerveau …). L’objectif de cette étude était de décrire les complications osseuses de la drépanocytose. Patients et Méthodes : Il s’agissait d’une étude rétrospective réalisée au service d’Hématologie – Oncologie du CHU de Donka qui s’est étalée sur une période de cinq ans (5ans) allant du 1 er janvier 2011 au 31 décembre 2015 Résultats : La fréquence des complications osseuses de la drépanocytose était de 15%. Il y avait une prédominance du sexe féminin avec le sex-ratio de 0,8. L’âge moyen des patients était de 27,5 ans avec des extrêmes de 10 et de 50 ans. Le principal motif de consultation était la douleur osseuse retrouvée chez 100% de nos patients. L’ostéomyélite était la complication la plus fréquente soit 55,56 % suivie de la nécrose de la tête fémorale soit 44,44%. Conclusion : Il est ressorti de l’étude que la prévalence des complications osseuses est non négligeable. Une étude prospective et analytique avec un échantillon plus élevé serait nécessaire pour identifier les facteurs de risque et élaborer un protocole de prise en charge